Biomechanical characteristics of self-expanding sinus stents during crimping and deployment_A comparison between different biomaterials. (February 2023) - Lu, Yung-Chang; Hsu, Lin-I; Lin, Chih-Feng; Hsu, Chi-Pin; Chang, Ting-Kuo; Cheng, Chung-Chih; Huang, Chang-Hung
Abstract: Self-expanding sinus stents are often used in functional endoscopic sinus surgery to treat inflamed sinuses. The PROPEL self-expanding sinus stent offers mechanical support to the sinus cavity to prevent restenosis. The stent is made of a bioabsorbable material (PLGA) that disappears after wound healing. However, complications such as foreign body sensation and severe stent migration/expulsion have been reported after implantation. Little is known about the contact characteristics of self-expanding sinus stents from when the stent is crimped into the insertion device through to deployment into the sinus cavity. This current study developed a test platform to analyze the biomechanical behavior of the stent during this process. Three common bioabsorbable materials, PLGA, PCL and Mg alloy, were evaluated to understand how the choice of material affects the biomechanical characteristics of self-expanding sinus stents. The results showed that the material can have a considerable influence on the contact characteristics during crimping and deployment. When crimped, the PLGA and Mg alloy stents showed much higher plastic strain and contact stress than the PCL stent. When deployed, the PCL stent had the largest contact area (4.3 mm 2 ) and the lowest contact pressure (0.1 MPa) on the inner surface of the sinus canal. The results indicate that PCL could be a suitable choice for self-expanding sinus stents. This current study provides a method for observing the biomechanical characteristics of sinus stents during stent crimping and deployment. Graphical abstract: Image 1